Maqasid Al-Shari'ah in business transactions: Special focus on sukuk as islamic project finance - Mohamad, Muhammad Hisyam; Ahmad Sarkawi, Azila (2011)

(untitled)
One of the social aspects in maqasid al-shari’ah relating to business transactions is joint venture. The idea is well established in Islam with Quranic injunction that “...help one another in furthering virtue and God consciousness, and not in what is wicked and sinful...”(Al-Ma’idah:2). It can be implied in business transactions (mu’amalat) principally through its concepts of risk sharing, musharakah and mudharabah (partnership) where the ultimate aim is inviting good and forbidding bad i.e. maqasid al-shari’ah. Whereby, conventionally, joint ventures are examples of the strategic alliances which are often established between or among business enterprises. Having said that, it is the objectives of the paper to embed the Islamic concept of maqasid al-shari’ah (the objectives of Islamic law) in the mu’amalat system and to disclose the idea of sukuk as a means for Islamic project finance. The paper adopts qualitative methods which deploys library research and document analysis. It appears to be exploratory as the information required is subjective in nature, for instances the Islamic concepts of maqasid al-shari’ah in mua’malat system and sukuk as Islamic project finance. It was found that the considerations of maqasid al-shari’ah are no exception in construction works to ensure its sustainability. Furthermore, sukuk and its various types provide options for project finance. Thus, it is important for the maqasid al-shari’ah and sukuk to be considered and implemented in construction works.